A Catalog and Classification of Fortan Refactorings - Méndez, Mariano (2010)
This paper presents a catalog of code refactorings that are intended to improve different quality attributes of Fortran programs. We classify the refactorings according to their purpose, that is, the internal or external quality attribute(s) that each refactoring targets to improve. We sketch the implementation of one refactoring in Photran, a refactoring tool for Fortran.